A semi-automatic computer-aided method for personalized Vacuum Bell design. Issue 2 (4th March 2018) - Carfagni, Monica; Facchini, Flavio; Furferi, Rocco; Ghionzoli, Marco; Governi, Lapo; Messineo, Antonio; Servi, Michaela; Uccheddu, Francesca; Volpe, Yary
ABSTRACT: Pectus Excavatum, one of the most frequent chest wall deformities, is characterized by a depression of the sternum and costal cartilages. Patients with mild deformities are generally treated conservatively by using the so called Vacuum Bell (VB) i.e. a suction cup to be placed on the patient's sternal region. Three different sizes, as well as a model fitted for young women, of VB are available on the market. Unfortunately, the variability of the surface to be treated, the possible asymmetry of the caved-in area and the prolonged use, can make the device uncomfortable and, in some cases, ineffective for the patient. In order to cope with these issues, the present paper proposes a computer-aided method for customized vacuum bell design to be used by non-expert user, e.g. by medical staff. In particular, the present work entails the development of a system comprising: 1) a dedicated software capable of acquiring the 3D chest geometry - by using a low-cost range sensor, i.e. Kinect v2 - and of processing the point cloud so to generate NURBS surfaces of the chest; 2) a procedural CAD modeling of a personalized VB implemented within Siemens NX 11 CAD environment. Using the devised method, the medical staff is required only to use the 3D scanning system for acquiring the patient chest and to sketch, in a CAD-based interface, the boundary of the area to be treated. Once these tasks are performed, the system automatically builds the personalized VB model, ready to be manufactured. GRAPHICAL ABSTRACT: